1998
DOI: 10.1017/s0048577298970536
|View full text |Cite
|
Sign up to set email alerts
|

Probing affective pictures: Attended startle and tone probes

Abstract: Reflexive eyeblinks to a startle probe vary with the pleasantness of affective pictures, whereas the corresponding P300 varies with emotional arousal. The impact of attention to the probe on these effects was examined by varying task and probe type. Probes were either nonstartling tones or startling noises presented during affective picture viewing. Half the participants performed a task requiring attention to the probes; the other participants were told to ignore the probes. Blinks to the startle probe varied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
124
3
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(161 citation statements)
references
References 10 publications
31
124
3
2
Order By: Relevance
“…In line with that notion, enhancements of P3 during affective picture viewing have been observed in a number of studies, suggesting increased resource allocation to emotionally engaging stimuli (Cuthbert et al, 2000;Keil et al, 2002). Conversely, the P3 response to an acoustic startle probe presented during picture viewing shows the opposite pattern, with smaller probe P3 responses when participants concurrently view emotional, as opposed to neutral, pictures (Cuthbert et al, 1998;Schupp et al, 2004). That is, because motivationally relevant pictures utilize greater attentional resources than do neutral pictures, fewer are available for processing the startle probes.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…In line with that notion, enhancements of P3 during affective picture viewing have been observed in a number of studies, suggesting increased resource allocation to emotionally engaging stimuli (Cuthbert et al, 2000;Keil et al, 2002). Conversely, the P3 response to an acoustic startle probe presented during picture viewing shows the opposite pattern, with smaller probe P3 responses when participants concurrently view emotional, as opposed to neutral, pictures (Cuthbert et al, 1998;Schupp et al, 2004). That is, because motivationally relevant pictures utilize greater attentional resources than do neutral pictures, fewer are available for processing the startle probes.…”
supporting
confidence: 56%
“…We expected to replicate our previous finding of reduced P3 amplitude during affective picture viewing (Cuthbert et al, 1998), and further, to identify neural structures underlying this effect using the minimum norm source estimation approach. A more central research question concerns whether acoustic probe P3 modulation will be similar when the foreground modalities differ.…”
mentioning
confidence: 62%
“…Likewise, although emotional stimuli may evoke reflexive and involuntary processing under many conditions, this does not preclude that such effects can be amplified or attenuated by factors such as anxiety or attentional control capacity . In addition, experiments using crossmodal manipulations have demonstrated interactions between emotional and exogenous attention in the form of decreased P3 amplitude to auditory startle probes when emotionally intense visual stimuli are presented concurrently (Cuthbert, Schupp, Bradley, McManis, & Lang, 1998;Keil et al, 2007). In animal work, crossmodal interactions between different attention systems may even affect sensory processing at the level of sensory transduction (e.g., in the cochlea, see Delano, Elgueda, Hamame, & Robles, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The results of such studies have suggested that electrical responses in cortical pathways of sensory, perceptual, and cognitive processing are modulated by emotion in humans (Carretié, MartinLoeches, Hinojosa, & Mercado, 2001;Cuthbert, Schupp, Bradley, Birbaumer, & Lang, 2000;Cuthbert, Schupp, Bradley, McManis, & Lang, 1998;Kayser et al, 1997;Keil et al, 2002;Keil et al, 2001;Schupp et al, 2000). The studies converged to show a sustained late (Ͼ300 msec) positive potential (LPP) with a focus over the parietal scalp in response to emotionally arousing-either pleasant or unpleasant-pictures.…”
mentioning
confidence: 99%